A critical analysis of the linguistic and educational challenges facing Border-straddling speech communities, with special reference to the Nyanja-Chewa-Mang'anja cluster of Southeastern Africa - Nkhoma-Darch, Agnes Georgina Che-Jika (School of Education, 2015)
Bibliography: leaves 100-112.